Scheduled activity energy-aware distributed cluster- based routing algorithm for wireless sensor networks with non-uniform node distribution - Nokhanji, Nooshin (2014)
The main and definitive target of routing protocols in Wireless Sensor Networks (WSN) is passing data from the sensor nodes to the sink in most energy efficient manner besides considering the accuracy of data. Among different categories of routing protocols based on the network architecture, cluster-based (hierarchical) routing protocols are more energy efficient and increase the scalability as well as lifetime of the network. The non-uniform node deployment makes the energy consumption of the nodes more imbalanced. It makes the cluster-based routing protocols less efficient. Energy Aware Distributed Clustering (EADC) is one of the cluster-based routing protocol proposed for networks with non-uniform node distribution, which can effectively balance the energy consumption among the nodes. However, since the density of nodes varies in each region due to the non-uniform node deployment, in the dense area the sensed and transmitted data are extremely co-related and redundant. Therefore, the sensor nodes consume more inessential energy. Nevertheless, this unnecessary energy consumption is not considered in the EADC. Therefore, in this study, a new algorithm called Scheduled-Activity Energy Aware Distributed Clustering (SA-EADC) is proposed. SA-EADC adds another phase as “sensor redundancy check and activation” to EADC. It identifies the redundant sensor nodes, whose sensing coverage area are also covered completely by their direct neighbors and turns off them. In order to schedule the activity of these sensor nodes and to avoid creation of coverage holes, a distributed self-inactivation approach is proposed, in which the redundant sensor nodes work alternatively based on their residual energy. The proposed algorithm maintains the original sensing coverage, and guarantees sensing reliability. The results shows that SA-EADC algorithm can effectively identify the redundant nodes and schedule them to activate alternatively in a way that it reduces the overall system energy consumption and extends the network lifetime without degradation in coverage and sensing reliability of the network.